2004
DOI: 10.3127/ajis.v11i2.131
|View full text |Cite
|
Sign up to set email alerts
|

Does Touching a Projection Augmented Model and Interacting with it using a Spatially-Coincident Device, Affect a User's Perception of its Size?

Abstract: A Projection Augmented model (PA model) is a novel type of display. It consists of a real physical model, onto which a computer image is projected to create a realistic looking object. PA models provide their users with whole-hand haptic feedback and support spatially-coincident haptic interaction devices. This paper reports on an experiment that investigated the effect these factors have on a user's perception of the size a PA model. Results showed that touching a PA model increased the accuracy of size estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Moreover, it has been shown that touching a PA model can increase the degree of accuracy with which its geometric properties (e.g., size and shape) are perceived (Bennett & Stevens, 2004). PA models can also provide some haptic feedback for the material properties of the object that it is representing.…”
Section: Background: Projection Augmented Modelsmentioning
confidence: 98%
“…Moreover, it has been shown that touching a PA model can increase the degree of accuracy with which its geometric properties (e.g., size and shape) are perceived (Bennett & Stevens, 2004). PA models can also provide some haptic feedback for the material properties of the object that it is representing.…”
Section: Background: Projection Augmented Modelsmentioning
confidence: 98%